PENGARUH KEBUTUHAN SOSIAL DAN KEBUTUHAN AKTUALISASI DIRI TERHADAP KINERJA PEGAWAI MELALUI GAYA KEPEMIMPINAN SEBAGAI VARIABEL INTERVENING PADA PEGAWAI DINAS SOSIAL KABUPATEN LUWU - Nasruddin; Ilham Tahier; Andi Nadira Mahm (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
This study aims to examine how social needs and self-actualization needs affect employee performance through leadership style as an intervening variable at the Luwu Regency Social Service. This study uses the Smart PLS analysis tool is data processing software for Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The results concluded that the variables of social needs and self-actualization had a positive effect on the leadership style variable and the leadership style variable had a positive effect on employee performance. Social needs and self-actualization variables directly do not have a positive effect on employee performance variables. The results of hypothesis testing concluded that there was a positive effect of social needs variables on employee performance through leadership style as an intervening variable, while the self-actualization needs variable had a positive but not significant effect on employee performance through leadership style as an intervening variable